(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Objective.To Study Clinical Presentation, Management And Result Of Treatment Of 11 Consecutive Case Of Choledochal Cyst Managed From 2012 To 2019. Method.11 Children Presented With Upper Abdominal Pain(72.72%), Jaundice(27.27%), Mass (18.18%). Ultrasonograpy Diagnosed/Suugested In All 11 Children And Magnetic Resonance Cholangiopancreatigram Suggsted In 11 Patient. Result.9 Patient From 11 Children Have Type 1a (Cystic Dilation).2 Patient Have Type 1c(Fusiform Dilatation). Opertive Management Magement Included Primary Complete Excision Of Choledochal Cyst With Roux-En-Y Hepaticodochojejeunostomy(N=9),And Cyst Excision With Hepaticodochoduedenostomy(N=2).There Are 1 Post Operative Death Due To Deep Icterus And Poor General Condition Prior To Surgery.Short Term Follow Up Was Satisfactory In All 10 Patient. Conclusion.Choledochal Cyst Kept In Mind While Evalauting Children With Reccurent Upper Abdominal Pain And Jaundice.Primary Excision Of Choledochal Cyst With Roux-En Hepaticodochojejunostomy Providing Satisfactory Result In Management Of Vast Majoratity Of Case Of Choledochal Cyst In Childhood.